Exploring Students’ Experiences in Translating Cranford: A Narrative Inquiry Approach - Amaliya Syamsara; Annisa Meilyani; Elma Astutie; Marisa Shermia Nandha; Abdul Syahid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study explores an EFL student’s lived experience in translating Cranford using a narrative inquiry approach. Although the course initially focused on Cranford, the participant was assigned a different text, offering a distinct perspective on the challenges of literary translation. Data were gathered through reflective interviews and documentation of the translation process. The findings reveal the cognitive, emotional, and strategic aspects involved in literary translation. Initially overwhelmed and intimidated by the text’s complexity, the student gradually developed deeper interpretive skills, cultural sensitivity, and an appreciation for the expressive dimensions of translation. She utilized various strategies, such as close reading, repeated revisions, digital tools, and collaborative feedback. Ultimately, the student redefined translation not merely as a linguistic task but as a form of storytelling and creative interpretation. This study underscores the importance of authentic learning experiences and reflective practice in translator education.